EFFECT OF ANIMAL MANURE FERTILIZER APLICATION AND ECO-ENZYM DOSAGE ON CHLOROPHYLL CONTENT, YIELD AND QUALITY OF JAPANESE CUCUMBER (Cucumis sativus L. var Roberto) - Ajeng Wistika Dewi; Djuhari Djuhari; Anis Rosyidah (AGRONISMA, 2022)
Cucumber is one of the fruiting vegetable plants that is widely cultivated because it has benefits such as food, cosmetic ingredients, pharmaceutical ingredients and others. In Indonesia, cucumber production varies from year to year, efforts to increase cucumber yields are carried out using natural compost to further develop soil texture and structure, increase soil retention, and provide nutrients. This study aims to determine the effect of giving type of manure and dose of eco-enzyme on chlorophyll content, yield, and quality of Japanese cucumber. This research was carried out in Sekar Putih Hamlet, Pendem Village, Batu City with a factorial RAK consisting of 2 factors each consisting of 3 levels, namely the first factor P1 = Cow dung fertilizer, P2 = Goat dung fertilizer, and P3 = Chicken manure fertilizer, whereas the second factor is E1 = 0.5 recommended dose (3 liters ha-1), E2 = 1 recommended dose (6 liters ha-1) E3= 1.5 recommended doses (9 liters ha-1). Of the two factors, there ara 9 combinations 3 replications x 3 sampels = 81 experimental units. Data analysis used Anova 5% if it was tested further using a BNJ 5%. The results showed that the combination of goat manure and eco-enzyme dose of 6 liters ha-1 had a significant effect on chlorophyll content, yield and quality of cucumbers, but had no effect on chlorophyll levels at 50 and 55 days after planting and total dissolved solids.